Preparation method of diatomite composite catalytic material
Through acid leach modification and hydrothermal reaction, and combined with carbon paper electrode preparation method, the problem of many impurities and poor porosity of the diatomaceous earth catalyst support is solved, and efficient electrocatalytic reduction of carbon dioxide is achieved, which significantly reduces the amount of precious metals used and catalyst costs.
Patent Information
- Application Number
- CN202411792643.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-07
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-07
Smart Images

Figure CN119615253A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite material catalysis, and in particular relates to a method for preparing a diatomite composite catalytic material. Background Art
[0002] The extensive use of fossil fuels has caused serious air pollution, climate warming and energy crisis. The development of clean renewable energy has become a top priority. In order to achieve carbon emission reduction and full utilization of renewable energy, energy conversion and storage technologies represented by electrocatalytic carbon dioxide reduction are crucial. Highly active electrocatalysts are the key to efficient reduction of CO2.
[0003] Among the various heterogeneous catalysts involved, precious metal catalysts such as Pt, Pd, Au, Ag and other catalysts show significant low-temperature catalytic activity. However, due to the high cost of precious metals, the use of catalysts developed with precious metals is very limited under actual conditions. The introduction of supported catalysts provides a practical way to resolve the above contradictions. Paying attention to and selecting suitable carriers can effectively regulate the growth of supported metals and improve the synergistic catalytic performance of the overall catalyst, thereby achieving the goal of efficient and low-cost synergistic catalysis.
[0004] At present, the carriers used in industrial catalysts include molecular sieves, honeycomb ceramics, activated carbon, zeolite, montmorillonite, porous foam metal, diatomaceous earth and kaolin. my country has abundant reserves of high-quality diatomaceous earth. For example, diatomaceous earth in different forms is produced in Changbai Mountain, Jilin and Quzhou City, Zhejiang. It is a very good carrier choice with low cost. Obviously, making full use of the advantages of local diatomaceous earth resources and using readily available diatomaceous earth as a carrier can effectively reduce the high cost of catalysts.
[0005] Diatomaceous earth is a biogenic siliceous sedimentary rock composed of amorphous SiO2. It has many practical advantages and is a suitable industrial catalyst carrier. For example, diatomaceous earth has a unique microporous structure. As a support, it can effectively help capture and diffuse carbon dioxide, thereby improving the reaction mass transfer. Diatomaceous earth itself has a large specific surface area, providing many sites for the loading of precious metal catalysts, and it is expected to regulate the growth of nanocatalysts through reaction conditions. Diatomaceous earth has good adsorption properties. As a catalyst carrier, it can effectively adsorb carbon dioxide, which helps the contact and activation of reactants and catalyst active sites. After modification and screening, the SiO2 content of diatomaceous earth itself is as high as 98% or more, and it has good thermal stability, which helps to improve the stability of the catalyst. Diatomaceous earth itself does not contain chemical toxic substances. When used as a catalyst carrier for catalytic reduction reactions, it will not release toxic substances, which is green and environmentally friendly.
[0006] However, despite the above advantages of diatomite, it still has certain disadvantages when used as a catalyst carrier in specific application scenarios. For example, there are many impurities in diatomite minerals (such as viscosity, etc.), which makes it difficult to achieve fine control of the loading of metal active components in the catalyst; there are large differences in the morphology of diatomite from different origins, which leads to different main parameters of the carrier such as porosity and mechanical strength, and affects the loading control of metal active components, thereby affecting the performance of the catalytic material; in the aqueous environment solution, there are a large number of silanol groups on the surface and micropores of diatomite, and there are hydrogen bonds, which show hydrophilicity, will inhibit the yield of CO, and is not conducive to the generation of high-purity carbon products.
[0007] Therefore, it is necessary to further modify the diatomaceous earth raw materials for use in the preparation of catalytic materials to meet the technical requirements of more application scenarios. Summary of the invention
[0008] The technical problem to be solved by the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a diatomite composite catalytic material.
[0009] To solve the technical problem, the solution of the present invention is:
[0010] A method for preparing a diatomite composite catalytic material is provided, comprising the following steps:
[0011] (1) Acid leaching modification of diatomite
[0012] The crushed diatomite ore is added into an acid solution and subjected to acid leaching treatment under stirring; after natural sedimentation, the precipitate is taken out, centrifuged and washed with distilled water, mixed with an alkali solution, and the pH value is adjusted to a weak alkaline state; the obtained mixture is fully dispersed, sieved, and dried to obtain modified diatomite;
[0013] (2) Loading of precious metal active components
[0014] Take a noble metal nitrate aqueous solution, modified diatomaceous earth and an appropriate amount of distilled water, mix them at room temperature and perform ultrasonic treatment; transfer the mixture to a reactor, add a sodium citrate solution under stirring conditions, and close the reactor for hydrothermal reaction; in the hydrothermal reaction system, the mass ratio of the noble metal element: modified diatomaceous earth: water: sodium citrate is 0.4-10.8:100:8:1.03-103; after the reaction is completed, filter and wash the reaction product, and dry the solid to obtain a catalyst semi-finished product;
[0015] (3) Activation of composite catalytic materials
[0016] The composite catalytic material is activated in any of the following ways:
[0017] (3.1) grinding the catalyst semi-finished product into powder, adding it to a distilled water-ethanol-phenol mixture for ultrasonic dispersion; dropping the dispersion onto one side of a hydrophobic carbon paper, drying at room temperature to obtain a carbon paper used as an electrode, on which a diatomaceous earth composite catalytic material is loaded; or,
[0018] (3.2) Grind the catalyst semi-finished product into powder and add it to distilled water or ethanol solution for dispersion; take the dispersion and drop it onto one side of the hydrophobic carbon paper, dry it at room temperature, and then calcine it using Joule heat method to obtain carbon paper that can be used as an electrode, on which the diatomaceous earth composite catalytic material is loaded.
[0019] As a preferred embodiment of the present invention, in the step (1), the acid solution is a hydrochloric acid solution, a nitric acid solution, a sulfuric acid solution or a citric acid solution with a concentration of 1 to 3 mol / L, the temperature during the acid leaching treatment is 20 to 100°C, and the time is 1 to 3 hours; the alkali solution is a potassium hydroxide solution with a concentration of 2 mol / L.
[0020] As a preferred embodiment of the present invention, in the step (1), the number of centrifugal washings is 3 times, and the pH value is adjusted to 9-10; the monomer structure length of the modified diatomaceous earth after sieving and drying is 8-15 μm.
[0021] As a preferred embodiment of the present invention, in step (2), the precious metal element is at least one of palladium, silver, ruthenium or rhodium; the concentration of the precious metal nitrate aqueous solution is 0.001 to 0.025 mol / L, and the concentration of the sodium citrate solution is 0.002 to 0.2 mol / L.
[0022] As a preferred embodiment of the present invention, in the step (2), when the precious metal nitrate aqueous solution, modified diatomaceous earth and distilled water are mixed, ultrasonic treatment is first performed for 10 minutes, and then stirring is maintained at room temperature for 20 to 40 minutes; when the sodium citrate solution is added, the stirring speed is maintained at 500 to 900 rpm; the temperature of the hydrothermal reaction is 130 to 150° C., and the time is 3 to 5 hours.
[0023] As a preferred embodiment of the present invention, in step (2), the reaction product is filtered and then washed several times with distilled water and ethanol respectively, and the obtained solid is placed in an oven at 60° C. and dried for 5 to 7 hours.
[0024] As a preferred embodiment of the present invention, in the step (3), the ultrasonic dispersion time is 2 hours.
[0025] As a preferred embodiment of the present invention, in step (3), the amount of dispersion added is controlled so that the loading amount of the noble metal active component on the carbon paper is 0.01 to 0.27 mg / cm 2 .
[0026] As a preferred embodiment of the present invention, in the step (3.2), during the calcination process using the Joule heat method, the parameters are controlled to be: 20-60V, 5-10A, 0.01-0.05s, and a single pulse current conduction.
[0027] The present invention further provides a method for using the carbon paper loaded with diatomaceous earth composite catalytic material prepared by the aforementioned method in the electrocatalytic reduction of CO2, wherein the carbon paper is used as a working electrode to form a three-electrode together with an Ag / AgCl reference electrode and a platinum counter electrode; a KHCO3 solution is used as an electrolyte, and the catalyst overpotential and current density are obtained through an electrochemical workstation, thereby reducing CO2 gas to CO.
[0028] Description of the invention principle:
[0029] The diatomite composite catalytic material provided by the present invention has the characteristics of high activity and high stability, and has a relatively low content of noble metal active components and non-noble metal additives. Its developed pore structure can effectively capture carbon dioxide in the air, and can effectively convert carbon dioxide and water into a mixed gas of carbon monoxide and hydrogen at room temperature without heating or illumination, and is suitable for a variety of carbon dioxide conversion and energy storage devices. In addition, the preparation method adopted by the present invention is simple to operate, has strong universality, and the raw materials are cheap and easy to obtain, which is suitable for large-scale preparation of industrial catalysts.
[0030] Diatomite usually has unique morphological characteristics that vary from region to region, and may show different porosity and adsorption characteristics. It is rare to find diatomite with only excellent characteristics and very few inferior qualities. Therefore, in order to expand the market application of various diatomite raw materials and enhance their commodity value, it is necessary to conduct a comprehensive modification and screening process of acid leaching, alkali neutralization and screening on diatomite with special structure, low purity, and more clay impurities, so as to remove impure minerals, etch to increase the surface roughness of diatomite, and remove agglomerated clay blocks and small fragments. This comprehensive process is used to help obtain high-purity diatomite with special morphological structure, which is beneficial to the loading and morphology regulation of precious metal active components.
[0031] On the basis of modifying diatomite, the present invention further realizes the uniform loading of precious metals on diatomite with specific morphology through a simple and easy synthesis process method; while maintaining the conversion efficiency of the catalyst in electrocatalytic reduction of carbon dioxide and water to carbon monoxide and hydrogen, the use of precious metals is greatly reduced, and the catalyst cost is significantly reduced.
[0032] The present invention can achieve nanoscale size regulation of metals loaded on diatomite by adjusting process parameters, thereby effectively controlling the ratio of carbon monoxide and hydrogen generated by electrocatalytic reduction, and is applied to different environmental requirements.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The diatomaceous earth composite catalyst used in the present invention can effectively realize the electrocatalytic reduction of carbon dioxide to carbon monoxide, and has good conversion efficiency and carbon monoxide yield.
[0035] 2. The diatomite composite catalyst prepared by the present invention has a developed pore structure and a large specific surface area, which, on the one hand, helps to capture and diffuse carbon dioxide, and on the other hand, the rough carrier surface is conducive to the uniform dispersion of loaded precious metals, realizes the nanoscale growth of metal components, and comprehensively improves the reaction mass transfer and catalytic activity.
[0036] 3. The preparation process disclosed in the present invention has a simple flow and high repeatability. By adjusting simple experimental parameters, it can effectively complete the nanoscale morphology regulation of the loaded precious metal and realize the control of the ratio of carbon monoxide and hydrogen generated by the catalyst in the application of carbon dioxide-containing water environment.
[0037] 4. The diatomaceous earth composite catalyst used in the present invention greatly reduces the use of precious metals, significantly reduces costs, is environmentally friendly, has good thermal stability, and is more suitable for industrial-scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a SEM morphology image of the diatomite composite catalytic material of the present invention.
[0039] The corresponding magnifications of the regions in the figure are: (a) 100 times, (b) 500 times, (c) 5000 times, and (d) 10000 times. DETAILED DESCRIPTION
[0040] In order to clearly and completely describe the technical solutions in the embodiments of the present invention in combination with the embodiments of the present invention, it is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Part I Overview of the Implementation Scheme of the Invention
[0042] The method for preparing the diatomite composite catalytic material provided by the present invention comprises the following steps:
[0043] (1) Acid leaching modification of diatomite
[0044] The crushed diatomite ore is added to a hydrochloric acid solution, a nitric acid solution, a sulfuric acid solution or a citric acid solution with a concentration of 1 to 3 mol / L, and acid-leached at 20 to 100°C with stirring for 1 to 3 hours; after natural sedimentation, the precipitate is taken, centrifuged and washed three times with distilled water, and then mixed with a potassium hydroxide solution with a concentration of 2 mol / L, and adjusted to a weak alkaline (pH value to 9 to 10); the obtained mixture is fully dispersed, sieved, and dried to obtain a modified diatomite with a monomer structure length of 8 to 15 μm;
[0045] (2) Loading of precious metal active components.
[0046] Take a noble metal nitrate aqueous solution, modified diatomaceous earth and an appropriate amount of distilled water, first ultrasonically treat for 10 minutes, and then keep stirring at room temperature for 20 to 40 minutes; the noble metal element can be at least one of palladium, silver, ruthenium and rhodium; the concentration of the noble metal nitrate aqueous solution can be selected from 0.001 to 0.025 mol / L. Then move the mixture to a reactor, add a sodium citrate solution with a concentration of 0.002 to 0.2 mol / L at a stirring speed of 500 to 900 rpm, and then close the reactor for hydrothermal reaction at a reaction temperature of 130 to 150°C for 3 to 5 hours; in the raw materials of the hydrothermal reaction, the mass ratio of noble metal element: modified diatomaceous earth: water: sodium citrate is 0.4 to 10.8: 100: 8: 1.03 to 103. After the reaction is completed, the reaction product is filtered and washed several times with distilled water and ethanol respectively, and the obtained solid is placed in a 60°C oven to dry for 5 to 7 hours to obtain a catalyst semi-finished product;
[0047] (3) Activation of composite catalytic materials
[0048] The composite catalytic material is activated in any of the following ways:
[0049] (3.1) Grind the catalyst semi-finished product into powder, add it to a distilled water-ethanol-phenol mixture and perform ultrasonic dispersion for 2 hours; drip the dispersion onto one side of the hydrophobic carbon paper, and control the dripping amount of the dispersion so that the loading amount of the noble metal active component on the carbon paper is 0.01-0.27 mg / cm 2 After drying at room temperature, a carbon paper that can be used as an electrode is obtained, on which a diatomaceous earth composite catalytic material is loaded; or,
[0050] (3.2) Grind the catalyst semi-finished product into powder, add it to distilled water or ethanol solution and perform ultrasonic dispersion for 2 hours; take the dispersion and drip it onto one side of the hydrophobic carbon paper, and control the dripping amount of the dispersion so that the loading amount of the noble metal active component on the carbon paper is 0.01-0.27 mg / cm 2After drying at room temperature, the calcination was carried out by Joule heat method, and the parameters were controlled to be 20-60V, 5-10A, 0.01-0.05s, and a single pulse current was turned on. Finally, carbon paper that can be used as an electrode was obtained, and the diatomaceous earth composite catalytic material was loaded on the carbon paper.
[0051] In the above activation process, different methods of preparing electrodes were used. Among them, method (3.1) is the more mainstream ink method, in which ultrasonic treatment can help the catalyst to be fully dispersed on the conductive carbon paper, and the phenol in the mixed solution acts as a curing cross-linking agent to allow the catalyst and the conductive carbon paper to continuously have physical contact, thereby preparing an electrode activation catalyst. Method (3.2) is to use Joule heat calcination, which can also achieve the role of activating the catalyst by rapidly raising and lowering the temperature to allow the catalyst and the conductive carbon paper to contact and sinter.
[0052] Furthermore, the carbon paper can be used as a working electrode to form a three-electrode together with an Ag / AgCl reference electrode and a platinum counter electrode; a KHCO3 solution is used as an electrolyte, and the catalyst overpotential and current density are obtained through an electrochemical workstation, thereby reducing CO2 gas to CO.
[0053] Part II Specific Examples of the Embodiments of the Invention
[0054] Example 1
[0055] The diatomite composite catalytic material provided in this embodiment comprises 1 g of a modified diatomite carrier and 0.00004 mol of an active component Pd.
[0056] The preparation method is as follows:
[0057] S1, diatomite modification.
[0058] Step 1: Prepare 1 mol / L hydrochloric acid solution, weigh the crushed diatomaceous earth ore into the above acidic solution, and stir at 100°C for 2 hours.
[0059] Step 2: The solid-liquid mixture obtained in the first step is naturally precipitated to remove the solution, and mixed with distilled water and centrifuged for washing three times, and 2 mol / L sodium hydroxide solution is added dropwise to the suspension to adjust the pH value to 10.
[0060] Step 3: After the solid-liquid mixture obtained in the second step is fully dispersed, it is screened through 500 mesh, 1000 mesh, 1600 mesh, and 2000 mesh sieves in sequence, and the sieved material on the 1600 mesh sieve is selected and put into an oven for drying to obtain a large number of carriers with a single diatomaceous earth structure length of 8 to 15 μm for standby use.
[0061] S2. Loading of precious metal active components.
[0062] Step 1: prepare 0.001 mol / L palladium nitrate solution and 0.002 mol / L sodium citrate solution.
[0063] Step 2: Pipette 40 ml of palladium nitrate solution, 1 g of modified carrier and 20 ml of distilled water solution into a 100 ml beaker, ultrasonicate for 10 min, and stir at room temperature for 30 min.
[0064] Step 3: Transfer the above solution to a stirring and heating reactor, maintain a stirring speed of 500 rpm, slowly drop 20 ml of sodium citrate solution into the above mixture, seal the reactor, and heat to 150°C for 5 hours.
[0065] In the hydrothermal reaction system, the mass ratio of noble metal element: modified diatomaceous earth: water: sodium citrate is 0.43:100:8:1.03;
[0066] Step 4: Filter the mixture in the reactor, wash it with distilled water and ethanol for several times, and dry the obtained solid in an oven at 60°C for 6 hours to obtain a semi-finished catalyst.
[0067] S3. Electrode preparation.
[0068] The synthesized catalyst semi-finished product was lightly ground into powder, 10 mg was taken and ultrasonically dispersed with 20 μl distilled water, 60 μl ethanol solution and 20 μl phenol solution for 2 h, and then 10 μl of the mixed solution was dripped onto the surface of one side of the 0.7 cm*0.7 cm hydrophobic carbon paper; the dripping amount was controlled so that the loading amount of the noble metal active component on the carbon paper was 0.05 mg / cm 2 Wait for drying at room temperature to obtain carbon paper loaded with diatomaceous earth composite catalytic material.
[0069] Example 2
[0070] The diatomite composite catalytic material provided in this embodiment comprises 1 g of a modified diatomite carrier and 0.0001 mol of an active component Ag.
[0071] The preparation method is as follows:
[0072] S1, diatomite modification.
[0073] Step 1: Prepare 2 mol / L hydrochloric acid solution, weigh the crushed diatomite ore into the above acidic solution, and stir at 80°C for 3 hours.
[0074] Step 2: The solid-liquid mixture obtained in the first step is naturally precipitated to remove the solution, and mixed with distilled water and centrifuged for washing three times, and 2 mol / L sodium hydroxide solution is added dropwise to the suspension to adjust the pH value to 10.
[0075] Step 3: After the solid-liquid mixture obtained in the second step is fully dispersed, it is screened through 500 mesh, 1000 mesh, 1600 mesh, and 2000 mesh sieves in sequence, and the sieved material on the 1600 mesh sieve is selected and put into an oven for drying to obtain a large number of carriers with a single diatomaceous earth structure length of 8 to 15 μm for standby use.
[0076] S2. Loading of precious metal active components.
[0077] Step 1: prepare 0.0025 mol / L silver nitrate solution and 0.01 mol / L sodium citrate solution.
[0078] Step 2: Pipette 40 ml of silver nitrate solution, 1 g of modified carrier and 20 ml of distilled water solution into a 100 ml beaker, ultrasonicate for 10 min, and stir at room temperature for 20 min.
[0079] Step 3: Transfer the above solution to a stirring and heating reactor, maintain a stirring speed of 500 rpm, slowly drop 20 ml of sodium citrate solution into the above mixture, seal the reactor, and heat to 130°C for 5 hours.
[0080] In the hydrothermal reaction system, the mass ratio of noble metal element: modified diatomaceous earth: water: sodium citrate is 1.08:100:8:5.16;
[0081] Step 4: Filter the mixture in the reactor, wash it with distilled water and ethanol for several times, and dry the obtained solid in an oven at 60°C for 5 hours to obtain a semi-finished catalyst.
[0082] S3. Electrode preparation.
[0083] The synthesized catalyst semi-finished product was lightly ground into powder, 10 mg was taken and ultrasonically dispersed with 20 μl distilled water, 60 μl ethanol solution and 20 μl phenol solution for 2 h, and then 10 μl of the mixture was dripped onto the surface of one side of the 0.7 cm*0.7 cm hydrophobic carbon paper; the dripping amount was controlled so that the loading amount of the noble metal active component on the carbon paper was 0.17 mg / cm 2 Wait for drying at room temperature to obtain carbon paper loaded with diatomaceous earth composite catalytic material.
[0084] Example 3
[0085] The diatomaceous earth composite catalytic material provided in this embodiment comprises 1 g of a modified diatomaceous earth carrier and 0.00004 mol of an active component Ru.
[0086] The preparation method is as follows:
[0087] S1, diatomite modification.
[0088] Step 1: Prepare 3 mol / L hydrochloric acid solution, weigh the crushed diatomite ore into the above acidic solution, and stir at 20°C for 3 hours.
[0089] Step 2: The solid-liquid mixture obtained in the first step is naturally precipitated to remove the solution, and mixed with distilled water and centrifuged for washing three times, and 2 mol / L sodium hydroxide solution is added dropwise to the suspension to adjust the pH value to 10.
[0090] Step 3: After the solid-liquid mixture obtained in the second step is fully dispersed, it is screened through 500 mesh, 1000 mesh, 1600 mesh, and 2000 mesh sieves in sequence, and the sieved material on the 1600 mesh sieve is selected and put into an oven for drying to obtain a large number of carriers with a single diatomaceous earth structure length of 8 to 15 μm for standby use.
[0091] S2. Loading of precious metal active components.
[0092] Step 1: prepare 0.001 mol / L ruthenium nitrate solution and 0.008 mol / L sodium citrate solution.
[0093] Step 2: Pipette 40 ml of ruthenium nitrate solution, 1 g of modified carrier and 20 ml of distilled water solution into a 100 ml beaker, ultrasonicate for 10 min, and stir at room temperature for 30 min.
[0094] Step 3: Transfer the above solution to a stirring and heating reactor, maintain a stirring speed of 700 rpm, slowly drop 20 ml of sodium citrate solution into the above mixture, seal the reactor, and heat to 150°C for 5 hours.
[0095] In the hydrothermal reaction system, the mass ratio of noble metal element: modified diatomaceous earth: water: sodium citrate is 0.40:100:8:4.12;
[0096] Step 4: Filter the mixture in the reactor, wash it with distilled water and ethanol for several times, and dry the obtained solid in an oven at 60°C for 7 hours to obtain a semi-finished catalyst.
[0097] S3. Electrode preparation.
[0098] The synthesized catalyst semi-finished product was lightly ground into powder and ultrasonically dispersed on the surface of one side of the hydrophobic carbon paper with distilled water or ethanol solution; the amount of dropwise addition was controlled so that the loading amount of the noble metal active component on the carbon paper was 0.27 mg / cm 2 After drying at room temperature, the carbon paper loaded with diatomite composite catalytic material was obtained by calcination using Joule heat method (20V, 5A, 0.03s single pulse current conduction).
[0099] Example 4
[0100] The diatomite composite catalytic material provided in this embodiment comprises 1 g of a modified diatomite carrier and 0.0002 mol of an active component Rh.
[0101] The preparation method is as follows:
[0102] S1, diatomite modification.
[0103] Step 1: Prepare 3 mol / L hydrochloric acid solution, weigh the crushed diatomaceous earth ore into the above acidic solution, and stir at 100°C for 1 hour.
[0104] Step 2: The solid-liquid mixture obtained in the first step is naturally precipitated to remove the solution, and mixed with distilled water and centrifuged for washing three times, and 2 mol / L sodium hydroxide solution is added dropwise to the suspension to adjust the pH value to 9.5.
[0105] Step 3: After the solid-liquid mixture obtained in the second step is fully dispersed, it is screened through 500 mesh, 1000 mesh, 1600 mesh, and 2000 mesh sieves in sequence, and the sieved material on the 1600 mesh sieve is selected and put into an oven for drying to obtain a large number of carriers with a single diatomaceous earth structure length of 8 to 15 μm for standby use.
[0106] S2. Loading of precious metal active components.
[0107] Step 1: prepare 0.005 mol / L rhodium nitrate solution and 0.02 mol / L sodium citrate solution.
[0108] Step 2: Pipette 40 ml of rhodium nitrate solution, 1 g of modified carrier and 20 ml of distilled water solution into a 100 ml beaker, ultrasonicate for 10 min, and stir at room temperature for 30 min.
[0109] Step 3: Transfer the above solution to a stirring and heating reactor, maintain a stirring speed of 900 rpm, slowly drop 20 ml of sodium citrate solution into the above mixture, seal the reactor, and heat to 150°C for 5 hours.
[0110] In the hydrothermal reaction system, the mass ratio of noble metal element: modified diatomaceous earth: water: sodium citrate is 2.05:100:8:10.3;
[0111] Step 4: Filter the mixture in the reactor, wash it with distilled water and ethanol for several times, and dry the obtained solid in an oven at 60°C for 6 hours to obtain a semi-finished catalyst.
[0112] S3. Electrode preparation.
[0113] The synthesized catalyst semi-finished product was lightly ground into powder, 10 mg was taken and ultrasonically dispersed with 20 μl distilled water, 60 μl ethanol solution and 20 μl phenol solution for 2 h, and then 10 μl of the mixed solution was dripped onto the surface of one side of the 0.7 cm*0.7 cm hydrophobic carbon paper; the dripping amount was controlled so that the loading amount of the noble metal active component on the carbon paper was 0.01 mg / cm 2 Wait for drying at room temperature to obtain carbon paper loaded with diatomaceous earth composite catalytic material.
[0114] Example 5
[0115] This embodiment provides a diatomaceous earth composite catalytic material for electrochemically converting carbon dioxide into carbon monoxide, comprising 1 g of a modified diatomaceous earth carrier and 0.0002 mol of an active component Ag.
[0116] The preparation method is as follows:
[0117] S1, diatomite modification.
[0118] Step 1: Prepare 2 mol / L citric acid solution, weigh the crushed diatomite ore into the above acidic solution, and stir at 80°C for 2 hours.
[0119] Step 2: The solid-liquid mixture obtained in the first step is naturally precipitated to remove the solution, and mixed with distilled water and centrifuged for washing three times, and 2 mol / L sodium hydroxide solution is added dropwise to the suspension to adjust the pH value to 9.
[0120] Step 3: After the solid-liquid mixture obtained in the second step is fully dispersed, it is screened through 500 mesh, 1000 mesh, 1600 mesh, and 2000 mesh sieves in sequence, and the sieved material on the 1600 mesh sieve is selected and put into an oven for drying to obtain a large number of carriers with a single diatomaceous earth structure length of 8 to 15 μm for standby use.
[0121] S2. Loading of precious metal active components.
[0122] Step 1: prepare 0.005 mol / L silver nitrate solution and 0.04 mol / L sodium citrate solution.
[0123] Step 2: Pipette 40 ml of silver nitrate solution, 1 g of modified carrier and 20 ml of distilled water solution into a 100 ml beaker, ultrasonicate for 10 min, and stir at room temperature for 30 min.
[0124] Step 3: Transfer the above solution to a stirring and heating reactor, maintain a stirring speed of 700 rpm, slowly drop 20 ml of sodium citrate solution into the above mixture, seal the reactor, and heat to 140°C for 4 hours.
[0125] In the hydrothermal reaction system, the mass ratio of noble metal element: modified diatomaceous earth: water: sodium citrate is 2.16:100:8:20.6;
[0126] Step 4: Filter the mixture in the reactor, wash it with distilled water and ethanol for several times, and dry the obtained solid in an oven at 60°C for 5 hours to obtain a semi-finished catalyst.
[0127] S3. Electrode preparation.
[0128] The synthesized catalyst semi-finished product was lightly ground into powder and ultrasonically dispersed on the surface of one side of the hydrophobic carbon paper with distilled water or ethanol solution; the amount of dropwise addition was controlled so that the loading amount of the noble metal active component on the carbon paper was 0.13 mg / cm 2 After drying at room temperature, the carbon paper loaded with diatomite composite catalytic material was obtained by calcination using Joule heat method (30V, 8A, 0.03s single pulse current conduction).
[0129] Example 6
[0130] This embodiment provides a diatomaceous earth composite catalytic material for electrochemically converting carbon dioxide into carbon monoxide, comprising 1 g of a modified diatomaceous earth carrier and 0.001 mol of an active component Ag.
[0131] The preparation method is as follows:
[0132] S1, diatomite modification.
[0133] Step 1: Prepare 3 mol / L nitric acid solution, weigh the crushed diatomite ore into the above acidic solution, and stir at 80°C for 1 hour.
[0134] Step 2: The solid-liquid mixture obtained in the first step is naturally precipitated to remove the solution, and mixed with distilled water and centrifuged for washing three times, and 2 mol / L sodium hydroxide solution is added dropwise to the suspension to adjust the pH value to 9.
[0135] Step 3: After the solid-liquid mixture obtained in the second step is fully dispersed, it is screened through 500 mesh, 1000 mesh, 1600 mesh, and 2000 mesh sieves in sequence, and the sieved material on the 1600 mesh sieve is selected and put into an oven for drying to obtain a large number of carriers with a single diatomaceous earth structure length of 8 to 15 μm for standby use.
[0136] S2. Loading of precious metal active components.
[0137] Step 1: prepare 0.025 mol / L silver nitrate solution and 0.2 mol / L sodium citrate solution.
[0138] Step 2: Pipette 40 ml of silver nitrate solution, 1 g of modified carrier and 20 ml of distilled water solution into a 100 ml beaker, ultrasonicate for 10 min, and stir at room temperature for 40 min.
[0139] Step 3: Transfer the above solution to a stirring and heating reactor, maintain a stirring speed of 900 rpm, slowly drop 20 ml of sodium citrate solution into the above mixture, seal the reactor, and heat to 140°C for 3 hours.
[0140] In the hydrothermal reaction system, the mass ratio of noble metal element: modified diatomaceous earth: water: sodium citrate is 10.8:100:8:103;
[0141] Step 4: Filter the mixture in the reactor, wash it with distilled water and ethanol for several times, and dry the obtained solid in an oven at 60°C for 6 hours to obtain a semi-finished catalyst.
[0142] S3. Electrode preparation.
[0143] The synthesized catalyst semi-finished product was lightly ground into powder and dispersed on the surface of one side of the hydrophobic carbon paper with distilled water or ethanol solution; the amount of dropwise addition was controlled so that the loading amount of the noble metal active component on the carbon paper was 0.09 mg / cm 2 After drying at room temperature, the carbon paper loaded with diatomite composite catalytic material was obtained by calcination using Joule heat method (60V, 10A, 0.01s pulse current conduction).
[0144] Example 7
[0145] This embodiment provides a diatomaceous earth composite catalytic material for electrochemically converting carbon dioxide into carbon monoxide, comprising 1 g of a modified diatomaceous earth carrier and 0.0002 mol of an active component Ag.
[0146] The preparation method is as follows:
[0147] S1, diatomite modification.
[0148] Step 1: Prepare 2 mol / L sulfuric acid solution, weigh the crushed diatomite ore into the above acidic solution, and stir at 60°C for 2 hours.
[0149] Step 2: The solid-liquid mixture obtained in the first step is naturally precipitated to remove the solution, and mixed with distilled water and centrifuged for washing three times, and 2 mol / L sodium hydroxide solution is added dropwise to the suspension to adjust the pH value to 9.
[0150] Step 3: After the solid-liquid mixture obtained in the second step is fully dispersed, it is screened through 500 mesh, 1000 mesh, 1600 mesh, and 2000 mesh sieves in sequence, and the sieved material on the 1600 mesh sieve is selected and put into an oven for drying to obtain a large number of carriers with a single diatomaceous earth structure length of 8 to 15 μm for standby use.
[0151] S2. Loading of precious metal active components.
[0152] Step 1: prepare 0.005 mol / L silver nitrate solution and 0.04 mol / L sodium citrate solution.
[0153] Step 2: Pipette 40 ml of silver nitrate solution, 1 g of modified carrier and 20 ml of distilled water solution into a 100 ml beaker, ultrasonicate for 10 min, and stir at room temperature for 40 min.
[0154] Step 3: Transfer the above solution to a stirring and heating reactor, maintain a stirring speed of 700 rpm, slowly drop 20 ml of sodium citrate solution into the above mixture, seal the reactor, and heat to 140°C for 3 hours.
[0155] In the hydrothermal reaction system, the mass ratio of noble metal element: modified diatomaceous earth: water: sodium citrate is 2.16:100:8:20.6;
[0156] Step 4: Filter the mixture in the reactor, wash it with distilled water and ethanol for several times, and dry the obtained solid in an oven at 60°C for 7 hours to obtain a semi-finished catalyst.
[0157] S3. Electrode preparation.
[0158] The synthesized catalyst semi-finished product was lightly ground into powder and dispersed on the surface of one side of the hydrophobic carbon paper with distilled water or ethanol solution; the amount of dropwise addition was controlled so that the loading amount of the noble metal active component on the carbon paper was 0.21 mg / cm 2 After drying at room temperature, the carbon paper loaded with diatomite composite catalytic material was obtained by calcination using Joule heat method (20V, 5A, 0.05s pulse current conduction).
[0159] Part III. Comparative Examples Different from the Present Invention
[0160] Comparative Example 1
[0161] Refer to "H3PW 12 O 40 / Preparation, Characterization and Catalytic Synthesis of n-Butyl Acetate by Acid-Modified Diatomite Catalyst" (DOI: 10.16085 / j.issn.1000-6613.2019-0813), diatomite was impregnated with sulfuric acid of a certain concentration and calcined at high temperature to obtain the corresponding acid-modified diatomite. Compared with the modification method in Example 2, the obtained carrier has a smaller specific surface area, larger pore volume and average pore size, and it is difficult to support the growth of nano-sized precious metals under the same loading conditions, and the electrocatalytic performance is not ideal.
[0162] Comparative Example 2
[0163] In Comparative Example 2, the preparation process of the diatomite carrier is the same as that of Example 2, except that the catalyst loading operation uses copper nitrate solution to replace silver nitrate for synthesis preparation, and finally the copper is obtained on the diatomite in a dendrite-like growth, which is difficult to disperse. Under the same test conditions, the yield and conversion efficiency of electrocatalytic CO2 reduction of CO and H2 in aqueous solution are not ideal.
[0164] Comparative Example 3
[0165] Commercially available analytically pure diatomite (Tianjin Damao Chemical Reagent Factory, No. 3714) was purchased and subjected to the same catalyst loading operation as in Example 6. The purchased diatomite was more disc-shaped, with more broken components, smaller specific surface area than the diatomite used in the example, and higher purity. The size of the electrode loaded with precious metal components was larger, and the catalytic performance was not ideal under the same test conditions.
[0166] Comparative Example 4
[0167] In Comparative Example 4, the other material synthesis steps are the same as those in Example 6. In the activation of the composite catalytic material, the power-on time is extended to 0.2 s. It can be seen that the size of the loaded metal in the prepared electrode sheet is large and the distribution is uneven, which leads to unsatisfactory catalytic performance under the same test conditions.
[0168] Part IV Catalytic performance testing and data analysis
[0169] The test platform was constructed as follows to test the CO conversion rate in the electrocatalytic reduction of CO2.
[0170] At normal pressure, the carbon paper loaded with diatomite composite catalytic material was fixed with a glassy carbon electrode clamp as the working electrode, and the Ag / AgCl reference electrode and 0.5 cm 2 The platinum counter electrode was used as a three-electrode for catalytic performance testing. The electrolyte was a 0.5 mol / L KHCO3 solution. The CO2 flow rate was 22 sccm. The catalyst overpotential and current density were obtained through an electrochemical workstation, and the CO yield was analyzed using a chromatograph.
[0171] Test results of various embodiments:
[0172] Example 1: At room temperature and pressure, and a potential of -1.6 V, the catalyst current density is 10.8 mA / cm 2 , the CO conversion rate was 15.2%. The catalytic effect was stable after 480h of testing.
[0173] Example 2: Under normal temperature and pressure, and a potential of -1.6 V, the catalyst current density is 11.6 mA / cm 2 The CO conversion rate was 16.8%. The catalytic effect was stable after 480 hours of testing.
[0174] Example 3: Under normal temperature and pressure, and a potential of -1.6 V, the catalyst current density is 12.5 mA / cm 2 , the CO conversion rate was 15.0%. The catalytic effect was stable after 480h of testing.
[0175] Example 4: Under normal temperature and pressure, and a potential of -1.6 V, the catalyst current density is 11.0 mA / cm 2 The CO conversion rate was 14.5%. The catalytic effect was stable after 480 hours of testing.
[0176] Example 5: Under normal temperature and pressure, and a potential of -1.6 V, the catalyst current density is 15.2 mA / cm 2 The CO conversion rate was 25.2%. The catalytic effect was stable after 480 hours of testing.
[0177] Example 6: Under normal temperature and pressure, and a potential of -1.6 V, the catalyst current density is 14.8 mA / cm 2 , the CO conversion rate was 21.0%. The catalytic effect was stable after 480h of testing.
[0178] Example 7: Under normal temperature and pressure, and a potential of -1.6 V, the catalyst current density is 13.2 mA / cm 2 The CO conversion rate was 15.6%. The catalytic effect was stable after 480 hours of testing.
[0179] Comparative Example 1: At room temperature and pressure, and a potential of -1.6 V, the catalyst current density is 9.5 mA / cm 2 , the CO conversion rate was 6.4%. The catalytic effect was stable after 480h of testing.
[0180] Comparative Example 2: At room temperature and pressure, and a potential of -1.6 V, the catalyst current density is 10.3 mA / cm 2 The CO conversion rate was 3.8%. The catalytic effect decreased seriously after 480h of testing.
[0181] Comparative Example 3: At room temperature and pressure, and a potential of -1.6 V, the catalyst current density is 7.2 mA / cm 2 The conversion rate of CO was 4.4%. The catalytic effect was stable after 480 hours of testing.
[0182] Comparative Example 4: At room temperature and pressure, and a potential of -1.6 V, the catalyst current density is 11.4 mA / cm 2 The conversion rate of CO was 5.2%. The catalytic effect was stable after 480 hours of testing.
[0183] The final results are summarized in the following table:
[0184]
[0185] The following conclusions can be obtained from the test data of each embodiment and comparative example:
[0186] 1. The diatomite composite catalyst product of the present invention realizes the effective electrocatalytic reduction of CO2 to CO;
[0187] 2. The diatomaceous earth raw material and precious metal component selected in the embodiment increase the yield of the target product by 2 to 4 times compared with that in the comparative example, and have good stability;
[0188] 3. The present invention optimizes important indicators of the catalyst material such as target product yield, catalytic activity and working stability by adjusting parameters of the preparation and activation process. For example, the use of the Joule heat method to prepare the electrode in the present invention effectively removes the organic components of diatomite and further expands the pore structure of the material, while the sintering of the catalyst and the conductive carbon paper also enhances the conductivity of the electrode and improves the catalyst activity.
[0189] 4. The present invention can adjust the catalyst morphology and the final reduction product ratio by adjusting the material synthesis components and process parameters, which is sufficient to meet the needs of different working environments.
[0190] 5. The electrode sheet produced by the present invention has a simple operation process, short time, low cost, and is suitable for industrial-scale production.
[0191] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a diatomite composite catalytic material, characterized in that: The following steps are involved: (1) Acid leaching modification of diatomite The crushed diatomite ore is added into the acid solution and subjected to acid leaching treatment under stirring; After natural sedimentation, the precipitate is collected, washed by centrifugation with distilled water, mixed with alkali solution, and the pH value is adjusted to weak alkalinity; the obtained mixture is fully dispersed, sieved, and dried to obtain modified diatomaceous earth; (2) Loading of precious metal active components Take a noble metal nitrate aqueous solution, modified diatomaceous earth and an appropriate amount of distilled water, mix them at room temperature and perform ultrasonic treatment; transfer the mixture to a reactor, add a sodium citrate solution under stirring conditions, and close the reactor for hydrothermal reaction; in the hydrothermal reaction system, the mass ratio of the noble metal element: modified diatomaceous earth: water: sodium citrate is 0.4-10.8:100:8:1.03-103; after the reaction is completed, filter and wash the reaction product, and dry the solid to obtain a catalyst semi-finished product; (3) Activation of composite catalytic materials The composite catalytic material is activated in any of the following ways: (3.1) Grinding the catalyst semi-finished product into powder, adding it to a distilled water-ethanol-phenol mixture for ultrasonic dispersion; dropping the dispersion onto one side of a hydrophobic carbon paper, drying at room temperature to obtain a carbon paper used as an electrode, on which a diatomaceous earth composite catalytic material is loaded; or, (3.2) Grind the catalyst semi-finished product into powder and add it to distilled water or ethanol solution for dispersion; take the dispersion and drop it onto one side of the hydrophobic carbon paper, dry it at room temperature, and then calcine it using Joule heat method to obtain carbon paper that can be used as an electrode, on which the diatomaceous earth composite catalytic material is loaded.
2. The method according to claim 1, characterized in that In the step (1), the acid solution is a hydrochloric acid solution, a nitric acid solution, a sulfuric acid solution or a citric acid solution with a concentration of 1 to 3 mol / L, the temperature during the acid leaching treatment is 20 to 100°C, and the time is 1 to 3 hours; the alkali solution is a potassium hydroxide solution with a concentration of 2 mol / L.
3. The method according to claim 1, characterized in that In the step (1), the number of centrifugal washings is 3 times, and the pH value is adjusted to 9-10; the monomer structure length of the modified diatomaceous earth after sieving and drying is 8-15 μm.
4. The method according to claim 1, characterized in that: In the step (2), the precious metal element is at least one of palladium, silver, ruthenium or rhodium; the concentration of the precious metal nitrate aqueous solution is 0.001 to 0.025 mol / L, and the concentration of the sodium citrate solution is 0.002 to 0.2 mol / L.
5. The method according to claim 1, characterized in that In the step (2), when the noble metal nitrate aqueous solution, modified diatomaceous earth and distilled water are mixed, ultrasonic treatment is first performed for 10 minutes, and then stirring is maintained at room temperature for 20 to 40 minutes; when the sodium citrate solution is added, the stirring speed is maintained at 500 to 900 rpm; the temperature of the hydrothermal reaction is 130 to 150° C., and the time is 3 to 5 hours.
6. The method according to claim 1, characterized in that In the step (2), the reaction product is filtered and then washed several times with distilled water and ethanol respectively, and the obtained solid is placed in an oven at 60° C. and dried for 5 to 7 hours.
7. The method according to claim 1, characterized in that In the step (3), the ultrasonic dispersion time is 2 hours.
8. The method according to claim 1, characterized in that In the step (3), the amount of the dispersion added is controlled so that the loading amount of the noble metal active component on the carbon paper is 0.01 to 0.27 mg / cm 2 .
9. The method according to claim 1, characterized in that: In the step (3.2), during the calcination process using the Joule heat method, the parameters are controlled to be: 20-60V, 5-10A, 0.01-0.05s, and a single pulse current conduction.
10. A method for using the carbon paper loaded with diatomaceous earth composite catalytic material prepared by the method of claim 1 in electrocatalytic reduction of CO2, characterized in that: The carbon paper is used as the working electrode, and together with the Ag / AgCl reference electrode and the platinum counter electrode, a three-electrode is formed; a KHCO3 solution is used as the electrolyte, and the catalyst overpotential and current density are obtained through an electrochemical workstation, thereby reducing CO2 gas to CO.
Citation Information
Patent Citations
Preparation method of diatomite / molecular sieve composite material for adsorbing volatile organic pollutants
CN109304141A
Diatomite composite catalyst as well as preparation method and application thereof
CN113145111A
Pd (OH) 2 / diatomite catalyst as well as preparation method and application thereof
CN117718042A
Catalyst for preparing ethanol through acetic acid catalytic hydrogenation and preparation and application thereof
WO2014139064A1